Needle Revision with Antimetabolites in Bleb Failure - Ehab Ghoneim (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2014)
Glaucoma filtering surgery is unusual in that its goal is the creation and maintenance of a non healing fistula between two anatomic spaces that are normally not connected [1]. Fibroblasts, connective tissue elements, cytokines, aqueous humor and the surrounding vascular supply all influence what happens to a bleb over a long period of time. The enemy of drainage procedure is excessive scarring [2]. Long-term studies showed a loss of intraocular pressure (IOP) control in a significant proportion of eyes with an initially successful trabeculectomy [2,3]. So follow up of glaucoma patients after surgery is mandatory as significant proportion develop bleb failure. Revision of guarded filtration procedures was reported as early as 1941 by Ferrer [4]. Needling as currently performed was described by Pederson and Smith [5]. The combination of needling with antimetabolites (mitomycin C and 5FU) greatly improve the outcome of needling and enhance bleb survival.